2023
DOI: 10.36834/cmej.74949
|View full text |Cite
|
Sign up to set email alerts
|

A comparative analysis of graduate preparedness for a career in General Internal Medicine before and after national subspecialty recognition to inform curricular changes: have we met the mark?

Abstract: Background: A survey of General Internal Medicine (GIM) graduates published in 2006 revealed large training gaps that informed the development of the first national GIM objectives of training in 2010. The first recognized GIM certification examination was written by candidates in 2014. The landscape is again changing with the introduction in 2019 of competency-by-design (CBD) to GIM training. This study aims to examine pre-existing and emerging training gaps with standardization of GIM curricula and identify n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Samantha Halman and team wrote A comparative analysis of graduate preparedness for a career in General Internal Medicine before and after national subspecialty recognition to inform curricular changes: have we met the mark? 14 They found that that the standardization of the General Internal Medicine training closed many previously identified preparedness gaps. However, they noted that new skills, such as point-of-care ultrasound, will require deliberate implementation within the curricula.…”
Section: Original Researchmentioning
confidence: 99%
“…Samantha Halman and team wrote A comparative analysis of graduate preparedness for a career in General Internal Medicine before and after national subspecialty recognition to inform curricular changes: have we met the mark? 14 They found that that the standardization of the General Internal Medicine training closed many previously identified preparedness gaps. However, they noted that new skills, such as point-of-care ultrasound, will require deliberate implementation within the curricula.…”
Section: Original Researchmentioning
confidence: 99%